Factors associated with knowledge and vaccination intention for human papillomavirus on trans girls by their main caregiver: A cross-sectional study - Domínguez-Riscart, Jesus; Ariza-Jimenez, Ana-Belen; Baez-Castillo, Celia; Mateo-Gavira, Isabel (Frontiers in Immunology, 2023)
Trans women are highly affected by human papillomavirus(HPV) with the risk of suffering HPV related diseases such as oropharyngeal, anal, penile or neovaginal neoplasia. HPV vaccination seems to be a good strategy to reduce HPV related diseases, mainly in early ages before the first sexual intercourse, but only cisgender girls arecovered by National Health Services, while some risk groups as trans girls are not included. To achieve a high vaccination rate is important in the adolescent population but there are many factors which could affect it, such as lack of knowledge about HPV or fear of side effects by patients and main caregivers. The aim of our study is to analyze knowledge of trans girls´ main caregivers about HPV related disease in the general population, and in particular, in trans women, as well as factors associated with HPV vaccination intention. A cross-sectional study was performed with the collaboration of main caregivers of trans girl adolescents, between 9-16 years old, assisted in two reference centers ‘multidisciplinary Gender Diversity Units. Information was requested, through a self-completed questionnaire HPV related diseases Knowledge Transwomen questionnaire (HPV-TQ) was elaborated based on a 19-item self-administered questionnaire and score was standardized from 0-19 points. Percentage of correct answers were calculated and defined by the group of High score who showed over 70% correct answers. 65 main caregivers were included. Almost all main caregivers were mothers and Caucasian ethnic. HPV-TQ average score was 11 (3.7) with an average correct answer of 58.1% (19.6). Only 17/65 (26.1%) of main caregivers had high knowledge in HPV. 14/65 trans girls were already vaccinated (29.8% of trans girls over 12 years old). 78.5% were non vaccinated and only 21.5% had intention of vaccination. The group with high score in HPV-TQ had longer follow-up at the transgender unit, higher maternal vaccination, and a positive family history of HPV related disease, especially in mothers as well. Trans girls attended in our units had a low rate and intention of vaccination against HPV. Probably, Education, promotion and prevention on Transgender HPV related disease should be implemented to achieve a higher knowledge and vaccination coverage.